Maternal Fluoride Exposure Exerts Different Toxicity Patterns in Parotid and Submandibular Glands of Offspring Rats - Santos, Vinicius Ruan Neves dos; Ferreira, Maria Karolina Martins; Bittencourt, Leonardo Oliveira; Mendes, Paulo Fernando Santos; Souza-Monteiro, Deiweson; Balbinot, Karolyny Martins; Pinheiro, João de Jesus Viana; Charone, Senda; Pessan, Juliano Pelim [UNESP]; Lima, Rafael Rodrigues (MDPI, 2022)
There is currently a controversial and heated debate about the safety and ethical aspects of fluoride (F) used for human consumption. Thus, this study assessed the effects of prenatal and postnatal F exposure of rats on the salivary glands of their offspring. Pregnant rats were exposed to 0, 10, or 50 mg F/L from the drinking water, from the first day of gestation until offspring weaning (42 days). The offspring rats were euthanized for the collection of the parotid (PA) and submandibular (SM) glands, to assess the oxidative biochemistry and to perform morphometric and immunohistochemical analyses. F exposure was associated with a decrease in the antioxidant competence of PA in the 10 mg F/L group, contrasting with the increase observed in the 50 mg F/L group. On the other hand, the antioxidant competence of the SM glands was decreased at both concentrations. Moreover, both 10 and 50 mg F/L groups showed lower anti-α-smooth muscle actin immunostaining area in SM, while exposure to 50 mg F/L was associated with changes in gland morphometry by increasing the duct area in both glands. These findings demonstrate a greater susceptibility of the SM glands of the offspring to F at high concentration in comparison to PA, reinforcing the need to adhere to the optimum F levels recommended by the regulatory agencies. Such findings must be interpreted with caution, especially considering their translational meaning.
Keywords: cytoskeleton; fluoride; immunohistochemistry; salivary glands